(3bUjOJGfs - (3YeQ Hf YHO GdQMef, GdHGQ,J (B1158 (3g` s
(3ChdgG (B:s
(3gPg GdCHjGJ ddEeGe GdbWH YGe RjGQJg hMLg SfI (B1143(3g` bGdgG aj WjHI GdeTQaI cd jhe dfG HWjHI YjO hHgG LfI hYjT QZjO s
(3BNQgG (B:s
(3Ydjg UdGI Gddg Ke SdGeg Edi CHO GdBHGO ef HYO CMbH hBdg hCUMGH cQGe hJGHY Ydi GdHQ hGdJbhi haYd GdebQH s
(3Vef eLehY , JQJjHgG (B: (3ef U (B227 - (3U(B240s
(3HBNQ cd UaMI JYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B127 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs